Mekanisme Penyelesaian Sengketa WTO dalam Kasus Lisensi Impor Produk Holtikultura dan Hewan Indonesia - Salwa Hayati; Zahwa Tsamara Shafwah (Jurnal Ilmiah Hubungan Internasional Fajar, 2026)
This article examines the World Trade Organization’s Dispute Settlement Body (DSB) through the case Indonesia – Importation of Horticultural Products, Animals and Animal Products (DS477/DS478). Conceptually, the DSB ensures due process, transparency, and legal certainty under the DSU, moving through consultations, panel proceedings, Appellate Body review, adoption, and surveillance (WTO, 1994; Marceau, 2018). The literature positions DS477/DS478 as a landmark on how non- automatic import licensing via narrow application windows, short validity periods, minimum realization requirements, and time-of-year restrictions can amount to prohibited quantitative restrictions under GATT Article XI:1 (WTO, 2014; USTR, 2017; Dukgeun & Gnutzmann- Mkrtchyan, 2019). Indonesia’s defenses under Article XX failed to meet the standards of contribution, proportionality, and availability of less trade-restrictive alternatives (WTO, 2017a; Miryanti & Baniyah, 2023). After the ruling, Indonesia adjusted regulations (e.g., 2018 ministerial rules) to improve formal compliance, yet implementation challenges transparency, inter-agency coordination, and technical monitoring remained salient (Dianawati, 2021). The review underscores that import policy design must be evidence-based, proportionate, non- discriminatory, transparent, and predictable, so that legitimate objectives food security, farmer protection can be achieved without breaching multilateral trade disciplines. The findings offer lessons for developing members in balancing domestic regulatory autonomy with international obligations when crafting import licensing regimes. Keywords: WTO; DSB/DSU; import licensing; GATT Article XI; Article XX; DS477/DS478; implementation of the ruling.